Laboratory evaluation of species-dependent relative ionization efficiencies in the Aerodyne Aerosol Mass Spectrometer. Issue 6 (3rd June 2018) - Xu, Wen; Lambe, Andrew; Silva, Philip; Hu, Weiwei; Onasch, Timothy; Williams, Leah; Croteau, Philip; Zhang, Xuan; Renbaum-Wolff, Lindsay; Fortner, Edward; Jimenez, Jose L.; Jayne, John; et al.
ABSTRACT: Mass concentrations calculated from Aerodyne's aerosol mass spectrometers depend on particle collection efficiency (CE) and relative ionization efficiency (RIE, relative to the primary calibrant ammonium nitrate). We present new laboratory RIE measurements for a wide range of organic aerosol species (RIEOA ). An improved laboratory RIE calibration protocol with size and mass selection of calibrant particles and a light scattering-based detection of CE is used. Simpler calibrations of alcohol RIEs using binary mixtures with NH4 NO3 are demonstrated. Models that account for only thermal velocity and electron ionization of vaporized molecules do not reproduce RIEOA measurements, confirming that other processes are significant. The relationship between RIEOA and average carbon oxidation state ( ), a metric used to describe atmospheric OA, is investigated. An average RIEOA of 1.6 ± 0.5 (2σ) is found for −1.0 < < 0.5, a range consistent with most ambient OA except hydrocarbon-like organic aerosol (HOA) and cooking organic aerosol (COA). RIEOA from 2 to 7 are found for below and above this range. The RIEOA typically used for ambient OA (1.4 ± 0.3) is within the laboratory RIEOA measurement uncertainty of oxidized organic species, but is a factor of 2 to 5 lower than that of reduced species. Such biases in OA mass concentrations have not been observed in published field analyses. Chemically reduced ambient OA may have composition, phase states, or compensating CE effects that are not mimicked well in the laboratory. This work highlights the need for further ambient OA studies to better constrain the composition dependence of ambient RIEOA, and the need to always calibrate with the OA under study for laboratory experiments. Copyright © 2018 American Association for Aerosol Research